Platelet Count and Survival in Patients with Colorectal Cancer – a Preliminary Study - Monreal, Manuel; Fernandez-Llamazares, Jaume; Piñol, Marta; Julian, Joan Francesc; Broggi, Marc; Escola, Diana; Abad, Albert (Thrombosis and Haemostasis, 1998)
In a previous report we found an inverse correlation between pre-operative platelet count (PlC) levels and the risk of post-operative pulmonary embolism in patients undergoing hip surgery. In the present study, we prospectively evaluated the prognostic significance of pre-operative PlC levels on survival in 180 consecutive patients undergoing surgery for colorectal cancer. Other major clinicopathological parameters studied were age, gender, Dukes’ stage, duration of surgery, pre-operative haemoglobin levels and transfusion requirements.There were no significant differences in mean pre-operative PlC levels according to tumor stage. Thirty-three patients (18%) died during follow-up (3-23 months, median: 13 months). Univariate analysis (Kaplan-Meier estimates) showed that advanced tumor stage (p <0.001), duration of surgery (p <0.05) and a high pre-operative PlC level (p <0.001) were significantly associated to a poor survival. The multivariate Cox analysis revealed that tumor stage (RR:5.734; 95%C.I.: 2.644-12.44), a high pre-operative PlC level (RR: 2.467; 95%C.I.: 1.117-5.452), and to a lesser extent the patients’ age remained independent prognostic variables for mortality. The findings of this preliminary study may be of interest from the point of view of pathogenesis, but also clinically, since they might be used in the decision as to which patients or groups of patients should receive more aggressive therapeutic intervention.